Lethal Complications and Complex Genotypes in Shwachman Diamond Syndrome: Report of a Family with Recurrent Neonatal Deaths and a Case-Based Brief Review of the Literature - Danai Veltra; Nikolaos M. Marinakis; Ioannis Kotsios; Polyxeni Delaporta; Kyriaki Kekou; Konstantina Kosma; Joanne Traeger-Synodinos; Christalena Sofocleous (MDPI AG, 2024)
Shwachman Diamond Syndrome (SDS) is a multi-system disease characterized by exocrine pancreatic insufficiency with malabsorption, infantile neutropenia and aplastic anemia. Life-threatening complications include progression to acute myeloid leukemia (AML) or myelodysplastic syndrome (MDS), critical deep-tissue infections and asphyxiating thoracic dystrophy. In most patients, SDS results from biallelic pathogenic variants in the SBDS gene, different combinations of which contribute to heterogenous clinical presentations. Null variants are not well tolerated, supporting the theory that the loss of SBDS expression is likely lethal in both mice and humans. A novel complex genotype (SBDS:c.[242C>G;258+2T>C];[460-1G>A]/WFS1:c.[2327A>T];[1371G>T]) was detected in a family with recurrent neonatal deaths. A female neonate died three hours after birth with hemolytic anemia, and a male neonate with severe anemia, thrombocytopenia and neutropenia succumbed on day 40 after Staphylococcus epidermidis infection. A subsequent review of the literature focused on fatal complications, complex SBDS genotypes and/or unusual clinical presentations and disclosed rare cases, of which some had unexpected combinations of genetic and clinical findings. The impact of pathogenic variants and associated phenotypes is discussed in the context of data sharing towards expanding scientific expert networks, consolidating knowledge and advancing an understanding of novel underlying genotypes and complex phenotypes, facilitating informed clinical decisions and disease management.